Do financial and personal characteristics of the household become institutional shields from natural disasters? A closer look at Vietnamese rural areas - Nguyen, Thi Mai; Tran Le, Khanh Ngoc; Anh Nguyen, Ngoc Quynh (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2023)
To identify whether households’ financial and personal characteristics serve as institutional shields from natural disasters, we analyzed more than 2,027 households in rural Vietnam in the VARHS dataset from 2008 to 2016. Results show that households receiving an early warning, household size, and participation in organizations positively impact household income sources in agriculture, while natural disasters and expenditures hurt household income, with varying degrees of influence depending on the income source. Kinh households suffer less damage, especially during natural disasters, and their loss of agricultural income in that year is also less than that of ethnic minority households. The findings suggest that the government needs to pay more attention and give support to ethnic minority households and promote early warning to contribute to mitigating the negative impacts of disasters.